Review on Protection Against Transients and Surges in Power System - Norliza Abd. Razak; Hamadi (International ABEC, 2021)
The most essential issue for electricity providers to address is power distribution breakdowns. A surge is a voltage or current wave that occurs suddenly. It happened within the power system in a very brief period of time, usually a few milliseconds. Furthermore, a surge in the electrical system can be caused by lightning, utility switching, including capacitor switching, equipment switching, and switching inductive loads within a facility. Surge protection systems are widely used around the world. The term